2020
DOI: 10.1038/s41598-020-61701-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Timing of Radiotherapy Following Gross Total or Subtotal Resection of Glioblastoma: A Real-World Assessment using the National Cancer Database

Abstract: Hesham elhalawani, neil chevli, pamela K. Allen * & caroline chung * treatment for glioblastoma (GBM) includes surgical resection and adjuvant radiotherapy (Rt) and chemotherapy. the optimal time interval between surgery and Rt remains unclear. the national cancer Database (ncDB) was queried for patients with GBM. overall survival (oS) was estimated using Kaplan-Meier and log-rank tests. Univariate (UVA) and multivariable cox regression (MVA) modeling was used to determine predictors of OS. A total of 45,942 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 34 publications
1
30
0
2
Order By: Relevance
“… 31 A better survival was also observed for women in several large cohorts of the US NCDB in patients with a diagnosis of glioblastoma between 2004 and 2015, 7 32 33 independently of the extent of resection. 33 Improved survival in female glioblastoma patients has also been reported specifically in the elderly population using SEER data. 34 Similar results were obtained in an extensive cohort of 16’717 patients aged 65 years old or more, diagnosed from 2005 to 2011 in another US NCDB study.…”
Section: Sex-specific Differences In Outcomementioning
confidence: 85%
“… 31 A better survival was also observed for women in several large cohorts of the US NCDB in patients with a diagnosis of glioblastoma between 2004 and 2015, 7 32 33 independently of the extent of resection. 33 Improved survival in female glioblastoma patients has also been reported specifically in the elderly population using SEER data. 34 Similar results were obtained in an extensive cohort of 16’717 patients aged 65 years old or more, diagnosed from 2005 to 2011 in another US NCDB study.…”
Section: Sex-specific Differences In Outcomementioning
confidence: 85%
“…o For paediatric leukemic testicular relapse, 1. including DMG [51][52][53] (level 2). o Hypo-fractionation using 13 fractions of 3.0 Gy results in comparable overall survival rates in patients with DMG of pontine origin [51,53] (level 1) o The utility of systemic agents for newly diagnosed DMG of pontine origin remains unproven [54] (level 2) o A slightly improved outcome is observed in children who received lomustine in addition to temozolomide for subtotally-resected glioblastoma with MGMT overexpression [55] (level 2) o In adults with glioblastoma, delays >8 weeks in patients with GTR resulted in worse survival [56] (level 1) Recommendation o Hypo-fractionation using 3.0 Gy is an alternative to normofractionation to lower the treatment burden in patients with DMG of pontine origin [grade B], and for patients with HGG from non-pontine origin and unfavourable molecular profile (grade D).…”
Section: Leukaemiamentioning
confidence: 99%
“…Interestingly enough, our analysis suggests that for patients with residual disease or relapse, the time interval is a more important factor than for those with no sign of macroscopic disease at the onset of radiotherapy. The relation between residual disease and the impact of time interval has been previously observed by some of the authors [9][10][11], but each of them formed different conclusions. Based on our data, we speculate that in patients with residual disease, radiochemotherapy should be regarded as a salvage treatment and therefore initiated earlier.…”
Section: Discussionmentioning
confidence: 83%
“…Yusuf et al [27] found that a time interval of 22-42 days from surgery compared to patients that started RCT earlier was associated with a significantly reduced risk of death. Finally, a recent study by Buszek et al [11] showed that < 4 weeks' time interval negatively impacted the survival of the patients.…”
Section: Discussionmentioning
confidence: 96%